Evaluating the biological cycle and reproductive and population parameters of calliphora vicina (Diptera: Calliphoridae) reared on three different diets (2016)
This work was aimed at evaluating Calliphora vicina Robineau-Desvoidy (Diptera: Calliphoridae) life cycle, life tables, and reproductive and population parameters. This species is a necrophagous, synanthropic, cosmopolitan fly with broad distribution in the Neotropical region. Six successive generations from adult specimens collected in Bogota, Colombia, were analyzed in laboratory conditions. The fly's life cycle was evaluated, using a natural diet of pig's liver (L) and two artificial diets-milk powder and egg (ME) and powdered liver (PL). The species' longest life cycle duration (in days), from egg to pupa, was obtained with the ME diet (24.6 6 6.7) whereas the lowest value was recorded with the L diet (18.8 6 3.6). Female adult forms achieved high longevity values, this being highest in ME (102.8 6 3.6). The most efficient diets (L and ME) led to the following average reproductive and population values: 226.2 and 465.4 net reproductive rate (Ro), 22.2 and 47.1 cohort generation time (Tc), 0.24 and 0.13 intrinsic population growth rate (rm), and 1.27 and 1.13 finite rate of increase (k). The set of results (in terms of relatively high average values concerning the biological characteristics analyzed) showed the species' adaptability to the environmental and nutritional conditions established in a laboratory setting, thereby enabling their colonization. © The Authors 2016.